Associations of objectively measured physical activity and sedentary time with pregnancy-specific health-related quality of life. (January 2022) - Whitaker, Kara M.; Jones, Melissa A.; Wallace, McKenzie K.; Catov, Janet; Barone Gibbs, Bethany
Abstract: Purpose: To examine associations of objectively measured moderate-to-vigorous-intensity physical activity (MVPA) and sedentary behavior (SED) with pregnancy-specific health-related quality of life (QoL) across pregnancy trimesters. Materials and methods: Women (N=131, mean age 30.9 years ± 4.9) were recruited from two large health care systems in the United States. MVPA and SED were estimated using a waist-worn ActiGraph GT3X and thigh-worn activPAL3 micro, respectively, for seven days in each trimester of pregnancy. Questionnaires were administered in each trimester to assess pregnancy-specific health-related QoL using the Nausea and Vomiting of Pregnancy Specific health Related Quality of Life (NVPQoL) questionnaire. Mixed effects linear regression examined associations of MVPA and SED with the NVPQoL total score and domain-specific scores (physical symptoms, fatigue, emotions, and limitations) across trimesters. Results: The NVPQoL total score and domain-specific scores significantly varied across trimesters, with highest scores (indicating worse QoL) observed in the first trimester and lowest scores (indicating better QoL) in the second trimester. A 1-standard deviation (SD) increment in MVPA (16.0 min/day or 1.8%) was associated with better QoL as indicated by the lower NVPQoL total score (β=-4.06, p=0.024) and limitations score (β = -2.80, p<0.001). A 1-SD increment in SED (1.5 hr/day or 10.0%) was associated with worse QoL as indicated by the higher fatigue score (β = 0.82, p=0.041). Conclusions: Pregnancy-specific health-related QoL varies across trimesters. Both lower SED, and to a greater extent higher MVPA are potential behavioral targets for improving pregnancy-specific health-related QoL.